(untitled) (Journal of Naval Architecture and Marine Engineering, 2010)
The interaction of free convection with thermal radiation of a viscous incompressible unsteady MHD flow past a vertical cylinder with variable surface temperature and concentration is analyzed. The fluid is a gray, absorbing-emitting but non-scattering medium and the Rosseland approximation is used to describe the radiative heat flux in the energy equation. The governing equations are solved using an implicit finite-difference scheme of Crank-Nicolson type. Numerical results for the transient velocity, the temperature, the concentration, the local as well as average skin-friction, the rate of heat and mass transfer are shown graphically. It is observed that the presence of as well as increase in the magnetic field leads to decrease in the velocity field and rise in the thermal boundary thickness. The numerical predications have been compared with the existing information in the literature and good agreement is obtained. Keywords: Heat Transfer, radiation, finite-difference Scheme, vertical cylinder DOI: 10.3329/jname.v5i2.2615 Journal of Naval Architecture and Marine Engineering 6(1)(2009) 1-24